Alkali Phosphonate Metal-Organic Frameworks - Maares, Maria; Ayhan, M. Menaf; Yu, Kai B.; Yazaydin, A. Ozgur; Harmandar, Keyser; Haase, Hajo; Beckmann, Jens (Wiley-V C H Verlag Gmbh, 2019)
A new family of porous metal-organic frameworks (MOFs), namely alkali phosphonate MOFs, is reported. [Na2Cu(H(4)TPPA)].(NH2(CH3)(2))(2) (GTUB-1) was synthesized using the tetratopic 5,10,15,20-tetrakis[p-phenylphosphonic acid] porphyrin (H-8-TPPA) linker with planar X-shaped geometrical core. GTUB-1 is composed of rectangular void channels with BET surface area of 697 m(2) g(-1). GTUB-1 exhibits exceptional thermal stability. The toxicity analysis of the (H-8-TPPA) linker indicates that it is well tolerated by an intestinal cell line, suggesting its suitability for creating phosphonate MOFs for biological applications.
Keywords: alkali-phosphonate; metal-organic frameworks; porphyrin; thermal stability; toxicology